Cosmetico per il trattamento della vulvodinia - Torello, Giulio (2024)
Cosmetic, including:- water, in percentual weight comprised between 63.72% and 95.64%;- Palmitoylethanolamide, in percentual weight comprised between 0.04% and 0.6%;- freeze-dried Noni juice, in percentual weight comprised between 0.12% and 0.276%;- β- caryophyllene, in percentual weight comprised between 0.112% and 0.24%;- Myrrh extract, in percentual weight comprised between 0.08% and 0.12%;- 4-t-butylcyclohexanol, in percentual weight comprised between 0.04% and 0.3%;- glyceric extracts based on Echinacea and/or Calendula and/or Mallow and/or Chamomile, in percentage weight between 0.62% and 1.8%; and- tyndallized lactic ferments, in percentage weight between 0.08% and 0.408%.